A new species of Myoleja Rondani (Diptera: Tephritidae) from Turkey with a key to the known species of the genus - Han, Ho-Yeon; Kütük, Murat (Zootaxa, 2006)
Myoleja korneyevi, n. sp., is described and illustrated. Type specimens were collected from low vegetation in the highlands of Trabzon province in Turkey. A few additional specimens from Russian Caucasus were also recognized conspecific. They can be distinguished from the other four known species of Myoleja by the characteristic wing pattern. Photographs of the specimens and detailed illustrations of the genitalic structures are provided. As well, there is a key to all five recognized species of Myoleja. The identities of Spilographa caucasica Bigot, Euleia contemnens Hering and Pseudospheniscus desparatus Hering are discussed, and although these species have been recently placed in Myoleja, we consider they belong elsewhere.